Manfaat Filsafat Ilmu Bagi Pengembangan Kurikulum Manajemen Pendidikan Islam - Irawansyah, Melvin; Aulia, Nur Fitri; Subekti, Imam (Regalia Institute, 2024)
This article aims to determine the benefits of the philosophy of science in the development of Islamic educational institutions. Good and quality education must be built on a philosophical foundation and in-depth study. This article was written using a literature review research method with an analytical approach to various sources from books, journals and other relevant literature. The results of this research show that the philosophy of science provides a strong basis for the development of a holistic Islamic education curriculum, balanced between religious knowledge and world science, and capable of producing a generation that is intelligent, has morals, and is able to answer the challenges of the times.